Border Terriers under primary veterinary care in England: demography and disorders - O'Neill, D G; Darwent, E C; Church, D B; Brodbelt, D C (Canine Genetics and Epidemiology, 2017)
The Border Terrier is a working terrier type that is generally considered to be a relatively healthy and hardy breed. This study aimed to characterise the demography and common disorders of Border Terriers receiving veterinary care in England using de-identified electronic patient record data within the VetCompass™ Programme.
Keywords: ePrints migration